The relevance of category sexual division of labor to the analysis of work in contemporary morfologia. (Emancipação, 2016)
This article aims to reflect on the morphology of work in contemporary society, where we analyze the category sexual division of labor, conceptualizing and discussing their relevance for understanding the organization and the process of labor in contemporary capitalism. Methodologically, is characterized by a theoretical essay that seeks to demonstrate the importance and the necessity of that category to unravel fundamental aspects in studies of the working world in the face of changes and maintenance of the basic contradictions of this process. The discussion demonstrates the inequality faced by women in productive and reproductive sphere, as well as social relations continue to operate and to present through exploration, domination and oppression expressed by wage inequality, sexual division of labor exploitation in domestic work, high rates of violence against women, among other elements.
Keywords: Work. Sexual Division of Labor. Capitalism.